Bibliographic Works Written About The Scholars Of The Hanafi Sect - Себетов, Жаркынбай (Scientific Journal of Faculty of Theology, 2019)
Hanafi sect - one of the fiqh schools. The imam of this sect is Abu Hanifa. However, many scholars contributed to the development of the Hanafi school as a fiqh school. These scholars contributed to the expansion of the Hanefi school with their works, ideas, activities and students. Many works have been written in order to introduce and spread Hanafi scholars around the science. Information about these works will be given in our article.